Polyaniline composite tungsten-based material as well as preparation method and application thereof

By in situ growing polyaniline nanoflower structures on carbon paper electrodes, the problems of low specific capacitance and poor hydrophilicity of carbon electrodes in microbial fuel cells were solved, efficient power generation and pollutant degradation were achieved, and the conductivity and biocompatibility of the electrodes were improved.

CN120690872APending Publication Date: 2025-09-23INST OF OCEANOLOGY - CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510822522.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-19
Publication Date
2025-09-23

AI Technical Summary

Technical Problem

The carbon electrodes in existing microbial fuel cells have low specific capacitance and poor hydrophilicity, resulting in insufficient microbial attachment and power production, low electron transfer efficiency, poor long-term electrochemical stability, and performance degradation in complex biological environments.

Method used

Carbon paper electrodes are modified with polyaniline composite tungsten-based materials. By in situ growing polyaniline on the tungsten-modified carbon paper, a nanoflower structure is formed, which improves the conductivity and biocompatibility of the carbon paper and enhances electron transfer at the microorganism-electrode interface.

Benefits of technology

The power generation performance and pollutant degradation ability of microbial fuel cells have been improved, the charge transfer resistance is small, the output voltage and power are high, and the environmental pollutant removal rate is higher, showing excellent microbial fuel cell anode material performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120690872A_ABST
    Figure CN120690872A_ABST
Patent Text Reader

Abstract

The invention relates to the field of microbial fuel cells, in particular to a polyaniline composite tungsten-based material and a preparation method and application thereof. The preparation method comprises the following steps: putting a tungsten-based material modified carbon paper electrode into an aniline solution, dropwise adding an ammonium persulfate solution, continuously stirring to enable polyaniline to uniformly grow in situ, and drying after reaction to obtain the polyaniline composite tungsten-based semiconductor modified carbon paper. The specific surface area of the electrode is increased by utilizing the polyaniline nanostructure, and charge transfer between microorganisms and the electrode and energy storage of the battery are facilitated. Therefore, a device assembled by using the polyaniline composite tungsten-based semiconductor modified carbon paper composite electrode as an anode has excellent power output, and a promising choice is provided for the anode of a microbial fuel cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of microbial fuel cells, and in particular to a polyaniline composite tungsten-based material and a preparation method and application thereof. Background Art

[0002] Conductive polymers have attracted considerable attention due to their unique properties. These materials not only possess conductivity intermediate between that of insulators and metals, exhibiting excellent pseudocapacitive properties, but also offer advantages such as low density, easy processing, corrosion resistance, and the ability to form films over large areas. They hold great promise for application in a wide range of fields, including energy storage and conversion, sensors, and electromagnetic shielding. As the primary site for bioelectrochemical reactions and biofilm formation, the properties of the anode significantly influence the output power density and Coulombic efficiency of microbial fuel cells (MFCs). Current research focuses on overcoming key bottlenecks such as low electron transfer efficiency, slow biofilm formation, poor stability, and high cost. Development trends are focused on utilizing nanotechnology, surface engineering, and bioengineering to develop high-performance multifunctional composites, optimize three-dimensional structures, and precisely manipulate the bio-abiotic interface. Conductive polymers, with their tunable conductivity, electrocatalytic activity, and biocompatibility, offer a unique approach to improving MFC anode performance, particularly by enhancing electron transfer at the microbe-electrode interface. However, their poor long-term electrochemical stability, insufficient mechanical strength, and potential performance degradation in complex biological environments remain key challenges hindering their large-scale application. Summary of the Invention

[0003] The present invention addresses the problems of low specific capacitance and poor hydrophilicity of carbon electrodes, which result in insufficient microbial attachment and power generation. A polyaniline composite tungsten-based material, a preparation method, and its application in preparing anodes for microbial fuel cells are proposed.

[0004] To achieve the above purpose, the present invention adopts the following technical solutions:

[0005] A method for preparing a polyaniline composite tungsten-based material is characterized by placing a tungsten-modified carbon paper electrode in an aniline solution, adding ammonium persulfate solution dropwise, and continuously stirring to allow polyaniline to grow in situ uniformly (allowing polyaniline to grow in situ uniformly on the tungsten-modified carbon paper electrode). After the reaction, the material is dried to obtain a polyaniline composite tungsten-based semiconductor-modified carbon paper.

[0006] The tungsten-modified carbon paper electrode is a WO3-carbon paper or a WS2 / WO3-carbon paper electrode.

[0007] The preparation method of the WO3-carbon paper is as follows:

[0008] S1. Dissolve 1 g of Na2WO4·2H2O and 0.63 g of C2H2O4·H2O in 100 mL of water, add 0.8 g of thiourea to the solution, stir evenly, and adjust the pH of the solution to 2 with hydrochloric acid to obtain a hydrothermal reaction solution;

[0009] S2. The hydrothermal reaction solution in step S1 is placed in a hydrothermal reactor, the reactor is transferred to a blast drying oven, and the hydrothermal reaction is maintained at 160-200 ° C for 20-30h;

[0010] S3. Filter and repeatedly rinse the black solid obtained by the reaction with deionized water and ethanol; then dry the solid to obtain WO3 nanoparticle material.

[0011] S4. Mix 7.5 mg of WO3 nanoparticles with 60 μL of 5 wt% Nafion solution, 340 μL of deionized water, and 600 μL of anhydrous ethanol, and ultrasonicate to obtain a dispersion. Add the dispersion dropwise onto the treated carbon paper, and then dry the carbon paper to obtain WO3-carbon paper.

[0012] The preparation method of the WS2 / WO3-carbon paper is as follows:

[0013] S1. Dissolve 1 g of Na2WO4·2H2O and 1.26 g of C2H2O4·H2O in 100 mL of water, add 1.6 g of thiourea to the solution, stir evenly, and adjust the pH of the solution to 1 with hydrochloric acid to obtain a hydrothermal reaction solution;

[0014] S2. The hydrothermal reaction solution in step S1 is placed in a hydrothermal reactor, the reactor is transferred to a blast drying oven, and the hydrothermal reaction is maintained at 160-200 ° C for 20-30h;

[0015] S3. Filter and repeatedly rinse the black solid obtained by the reaction with deionized water and ethanol; then dry the solid to obtain WS2 / WO3 nanoparticle material.

[0016] S4. 7.5 mg of WS2 / WO3 particles were mixed with 60 μL of 5 wt% Nafion solution, 340 μL of deionized water, and 600 μL of anhydrous ethanol, and ultrasonically treated to obtain a dispersion. The dispersion was added dropwise onto the treated carbon paper, and then the carbon paper was dried to obtain WS2 / WO3-carbon paper.

[0017] The concentration of the ammonium persulfate solution is 0.4 mol / L, and the concentration of the aniline solution is 0.1 mol / L; the volume ratio of the dropwise added ammonium persulfate solution to the aniline solution should be 1:4.

[0018] The ammonium persulfate solution was added dropwise and stirred for 2 hours. After the reaction was completed, the electrode was taken out and rinsed thoroughly. Finally, the washed electrode was transferred to a blast drying oven and dried at 60° C. for 10 hours to obtain a polyaniline composite tungsten-based material.

[0019] A polyaniline composite tungsten-based material is obtained by the method, and a polyaniline composite tungsten-based material with a nano-flower-like structure is obtained by the method.

[0020] An application of the polyaniline composite tungsten-based material, and an application of the polyaniline composite tungsten-based material in preparing anode materials for microbial fuel cells.

[0021] An application of the polyaniline composite tungsten-based material, and an application of the polyaniline composite tungsten-based material in preparing anodes of microbial fuel cells.

[0022] An application of the polyaniline composite tungsten-based material, and an application of the polyaniline composite tungsten-based material in removing pollutants in the environment.

[0023] The beneficial effects of the present invention are:

[0024] The present invention utilizes PANI to combine carbon paper electrodes and tungsten-based semiconductors to modify carbon paper to obtain a polyaniline composite tungsten-based material. The resulting material has improved power generation performance and pollutant degradation capabilities; specifically:

[0025] 1. The present invention modifies a carbon-based anode by modifying a polyaniline composite tungsten-based material to obtain a microbial fuel cell anode. The electrode has low charge transfer resistance, high output voltage and output power, and good microbial fuel cell power generation performance.

[0026] 2. The carbon paper anode material modified with the polyaniline composite tungsten-based material prepared in the present invention has the advantages of a low contact angle and a higher environmental pollutant removal rate, and is a potential high-efficiency microbial fuel cell anode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 These are scanning electron microscope images of tungsten-based material particles, where (a) is the WO3-carbon paper electrode synthesized in Example 1; (b) is the WS2 / WO3-carbon paper electrode synthesized in Example 1.

[0028] Figure 2Scanning electron microscope images of the polyaniline composite tungsten-based material particles provided in the embodiments and comparative examples of the present invention, wherein (ac) are SEM images of the PANI-carbon paper electrode synthesized in the comparative example at 10μm, 5μm, and 1μm scales; (df) are SEM images of the PANI / WO3-carbon paper synthesized in Example 1 at 10μm, 5μm, and 1μm scales; and (gi) are SEM images of the PANI / WS2 / WO3-carbon paper synthesized in Example 2 at 10μm, 5μm, and 1μm scales.

[0029] Figure 3 XPS diffraction patterns of polyaniline composite tungsten-based material particles provided in an embodiment of the present invention, wherein (a) is the full spectrum of the PANI-carbon paper electrode synthesized in the comparative example; (b) is the O1s spectrum of the PANI-carbon paper electrode synthesized in the comparative example; (c) is the N1s spectrum of the PANI-carbon paper electrode synthesized in the comparative example; (d) is the full spectrum of the PANI / WO3-carbon paper electrode synthesized in Example 1; (e) is the O1S spectrum of the PANI / WO3-carbon paper electrode synthesized in Example 1; (f) is the N1s spectrum of the PANI / WO3-carbon paper electrode synthesized in Example 1; ( g) W4f spectrum of the PANI / WS2 / WO3-carbon paper electrode synthesized in Example 1; (h) full spectrum of the PANI / WS2 / WO3-carbon paper electrode synthesized in Example 2; (i) O1s spectrum of the PANI / WS2 / WO3-carbon paper electrode synthesized in Example 2; (j) N1s spectrum of the PANI / WS2 / WO3-carbon paper electrode synthesized in Example 2; (k) W4f spectrum of the PANI / WS2 / WO3-carbon paper electrode synthesized in Example 2; (l) S2p spectrum of the PANI / WS2 / WO3-carbon paper electrode synthesized in Example 2.

[0030] Figure 4 Contact angle diagrams of polyaniline composite tungsten-based material particles provided in the embodiments of the present invention, wherein (a) is the contact angle diagram of the control example carbon paper; (b) is the contact angle diagram of the PANI-carbon paper synthesized in the comparative example; (c) is the contact angle diagram of the PANI / WO3-carbon paper synthesized in Example 1; and (d) is the contact angle diagram of the PANI / WS2 / WO3-carbon paper synthesized in Example 2.

[0031] Figure 5 The potential energy and power diagram of the polyaniline composite tungsten-based material anode microbial fuel cell provided by the embodiment of the present invention, where (a) is the trend of the electromotive force changing with the current density, and (b) is the power density and polarization curve.

[0032] Figure 6 CV and EIS diagrams of the polyaniline composite tungsten-based material particle anode microbial fuel cell during acclimation provided by the embodiment of the present invention, where (a) is the CV curve of different bioanodes; (b) is the EIS curve of different bioanodes

[0033] Figure 7 This is a graph showing the removal rates of chemical oxygen demand (COD) and sulfate for a microbial fuel cell with a polyaniline composite tungsten-based material particle anode provided in an embodiment of the invention. DETAILED DESCRIPTION

[0034] The present invention is further described below with reference to specific examples, which are intended to help those skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.

[0035] Comparative Example

[0036] A method for preparing anode materials for microbial fuel cells comprises the following steps:

[0037] (1) Use 0.5 mol / L sulfuric acid solution to prepare 0.4 mol / L ammonium persulfate solution and 0.1 mol / L aniline mixed solution.

[0038] (2) Place the carbon paper electrode in the prepared aniline solution and stir continuously, and at the same time add ammonium persulfate solution (the addition time in this experiment is about 200 minutes). The volume ratio of the added ammonium persulfate solution to the aniline solution should be 1:4.

[0039] (3) After stirring for 2 hours, the electrode was removed and rinsed thoroughly. Finally, the washed electrode was transferred to a blower and dried at 60°C for 10 hours to obtain a PANI-carbon paper (PANI-CP) electrode (see Figure 2 in (ac).

[0040] Example 1

[0041] A method for preparing anode materials for microbial fuel cells comprises the following steps:

[0042] (1) Dissolve 1 g of Na2WO4·2H2O and 0.63 g of C2H2O4·H2O in 100 mL of deionized water and stir to dissolve. Then, add 0.8 g of thiourea to the solution and stir evenly. Adjust the pH of the solution to 2 with hydrochloric acid to obtain a hydrothermal reaction solution.

[0043] (2) transferring the hydrothermal reaction solution in step (1) into a hydrothermal reactor and then into a forced air drying oven, and maintaining the temperature at 180° C. for 24 h;

[0044] (3) The reaction product in step (2) was filtered and the black solid obtained by the reaction was repeatedly washed with deionized water and ethanol; the solid was then transferred to a forced air drying oven at 60° C. and dried overnight to obtain WO3 nanoparticles.

[0045] (4) The carbon paper electrode was washed alternately with deionized water and ethanol and dried in a blast drying oven. 7.5 mg of WO3 nanoparticles were mixed with 60 μL of 5 wt% Nafion solution, 340 μL of deionized water, and 600 μL of anhydrous ethanol, and ultrasonically treated to obtain a dispersion. The dispersion was added dropwise onto the treated carbon paper, and then the carbon paper was dried to obtain a WO3-carbon paper electrode (see Figure 1 (a)).

[0046] (5) Use 0.5 mol / L sulfuric acid solution to prepare 0.4 mol / L ammonium persulfate solution and 0.1 mol / L aniline mixed solution.

[0047] (6) Place the WO3-carbon paper electrode prepared in step (4) into the prepared aniline solution and stir continuously, and at the same time, add ammonium persulfate solution dropwise (the addition time in this experiment is about 200 minutes). The volume ratio of the added ammonium persulfate solution to the aniline solution should be 1:4.

[0048] (7) After stirring for 2 hours, the electrode was removed and rinsed thoroughly. Finally, the washed electrode was transferred to a blast drying oven and dried at 60°C for 10 hours to obtain a PANI / WO3-carbon paper (PANI / WO3-CP) electrode (see Figure 2 (df)).

[0049] Example 2

[0050] A method for preparing anode materials for microbial fuel cells comprises the following steps:

[0051] (1) Dissolve 1 g of Na2WO4·2H2O and 1.26 g of C2H2O4·H2O in 100 mL of deionized water and stir to dissolve. Then, add 1.6 g of thiourea to the solution and stir evenly. Adjust the pH of the solution to 1 with hydrochloric acid to obtain a hydrothermal reaction solution.

[0052] (2) transferring the hydrothermal reaction solution in step (1) into a hydrothermal reactor and then into a forced air drying oven, and maintaining the temperature at 180° C. for 24 h;

[0053] (3) The reaction product in step (2) was filtered and the black solid obtained by the reaction was repeatedly washed with deionized water and ethanol; the solid was then transferred to a forced air drying oven at 60° C. and dried overnight to obtain tungsten-based nanoparticle material (WS2 / WO3 nanoparticles).

[0054] (4) The carbon paper electrode was washed alternately with deionized water and ethanol, and dried in a blast drying oven. 7.5 mg of the WS2 / WO3 nanoparticles obtained in step (3) above were mixed with 60 μL of 5 wt% Nafion solution, 340 μL of deionized water, and 600 μL of anhydrous ethanol, and ultrasonically treated to obtain a dispersion. The dispersion was added dropwise to the treated carbon paper, and then the carbon paper was dried to obtain a WS2 / WO3-carbon paper electrode (see Figure 1 (b))).

[0055] (5) Use 0.5 mol / L sulfuric acid solution to prepare 0.4 mol / L ammonium persulfate solution and 0.1 mol / L aniline mixed solution.

[0056] (6) Place the WS2 / WO3-carbon paper electrode prepared in step (4) into the prepared aniline solution and stir continuously, and at the same time add ammonium persulfate solution dropwise (the addition time in this experiment is about 200 minutes). The volume ratio of the added ammonium persulfate solution to the aniline solution should be 1:4.

[0057] (7) After stirring for 2 hours, the electrode was removed and rinsed thoroughly. Finally, the washed electrode was transferred to a blast drying oven and dried at 60 ° C for 10 hours to obtain a PANI / WS2 / WO3-carbon paper electrode (PANI / WS2 / WO3-CP) (refer to Figure 2 in(gi)).

[0058] The polyaniline composite tungsten-based material prepared above was observed by SEM. Figure 1 It can be seen that the surface of the three modified electrodes grows PANI with sheet structure. The size of the PANI nanosheets is uniform, and the diameter of a single nanosheet is about 1μm. This in situ grown PANI significantly increases the roughness of the carbon fiber surface, which helps microorganisms to colonize and form biofilms on the electrode surface. At the same time, the special structure and properties of the nanosheets will increase the specific surface area of ​​the electrode, thereby increasing the electron transfer rate at the interface. WO3 and WS2 / WO3 as supporting materials have a significant impact on the generation morphology of PANI. Figure 2 As shown in (c, f, i), PANI aggregates into a spherical distribution on the surface of unmodified carbon fiber, while it tends to form a nanoflower-like structure on the surface of PANI / WO3-carbon paper and PANI / WS2 / WO3-carbon paper electrodes, thereby further increasing the area for electron transfer between microorganisms and electrodes.

[0059] The polyaniline composite tungsten-based material prepared above was observed by XPS analysis. Figure 3The O1s peak spectra for all three electrodes show two sub-peaks, corresponding to the lattice oxygen in WO3 and the adsorbed oxygen on the carbon paper surface after acid-heat treatment. Nitrogen atoms in different chemical environments can split the N1s peak into multiple sub-peaks, and analyzing these sub-peaks can reveal information about the structure and oxidation state of polyaniline. Figure 3 The three sub-peaks of the N1s peak in (c, f, j) correspond to pyridinic nitrogen, pyrrolic nitrogen, and graphitic nitrogen in the electrode material. For protonic acid-doped polyaniline, nitrogen may reside in its nitrogen-containing groups (amine, imine, etc.), and is always associated with the higher pyrrolic nitrogen peak in the middle of the spectrum. Figure 3 The four obvious peaks of W4f in (k) indicate the presence of W in PANI / WS2 / WO3-CP. 4+ and W 6+ , corresponding to the generation of WS2 and WO3.

[0060] The contact angle of the polyaniline composite tungsten-based carbon paper material obtained above was tested to compare the hydrophilicity of different modified electrodes (see Figure 4 ), and the unmodified carbon paper electrode was used as a control.

[0061] Depend on Figure 4 It can be seen that the transient contact angles of PANI-carbon paper, PANI / WO3-carbon paper, and PANI / WS2 / WO3-carbon paper are large. Figure 4 a) exhibits weak hydrophobicity, with a contact angle of 130.2°. The droplet is completely absorbed the moment it touches the other electrodes.

[0062] Example 3

[0063] A microbial fuel cell was constructed using the materials prepared in the above examples and comparative examples as the anode material, and a conductive carbon brush as the cathode. The anolyte composition was sodium lactate (5 g / L), KH2PO4 (0.5 g / L), NH4Cl (1 g / L), CaCl2·2H2O (0.06 g / L), Na2SO4 (1 g / L), MgSO4·7H2O (2 g / L), and yeast extract (1 g / L). The anolyte pH was adjusted to approximately 7.2 using NaOH solution. The catholyte was composed of K3[Fe(CN)6] (16.46 g / L), KCl (0.13 g / L), Na2HPO4 (11.4 g / L), NaH2PO4 (2.77 g / L), and NH4Cl (0.31 g / L). After the assembly was completed, the bacterial solution was mixed with the cooled fresh anolyte obtained after high temperature sterilization at 121°C (volume ratio of 1:4). The COD concentration in the mixed system was 3412.34 mg / L, and the initial SO4 2-The concentration was 5.57 mM / L. Cysteine ​​was then added to the anolyte, and nitrogen was bubbled through the solution for 40 minutes to remove dissolved oxygen and maintain an anaerobic environment in the chamber. The exposed electrodes of the fuel cell were connected via wires to a 1000Ω variable resistor. The voltage across the resistor was monitored in real time by a data acquisition card (DAQ 6008, USA).

[0064] When the voltage across the resistor drops below 50 mV, the anolyte is replaced, but 20 mL of the original anolyte containing the bacterial solution is retained to ensure rapid restart of the fuel cell. A pure carbon paper electrode is used as a control during the above measurement.

[0065] The bacterial solution was obtained by taking the flowback fluid from a shale gas well station in my country and adding it to a treated enrichment culture medium at room temperature. The culture medium was placed in a biochemical incubator at 30°C for one month, and the liquid was changed once a week during this period.

[0066] The enrichment was carried out by anaerobic culture by passing nitrogen gas through the enrichment liquid culture medium after high-pressure sterilization at 121° C. for 40 minutes.

[0067] The culture medium contains 1.0 g / L of NH4Cl, 0.5 g / L of K2HPO4·3H2O, 1.0 g / L of (NH4)2Fe(SO4)2·6H2O, 2.0 g / L of MgSO4·7H2O, 5.0 g / L of C6H5Na3O7·2H2O, 5.0 g / L of sodium lactate, 1.0 g / L of yeast extract, 1.0 mL / L of Wolfe's mineral solution, and 1.0 mL / L of Wolfe's vitamin solution per liter of water.

[0068] In addition, chemical oxygen demand (COD) and SO4 in the solution were measured at the beginning of the microbial fuel cell operation cycle. 2- Concentration; Chemical oxygen demand (COD) in the anolyte was determined by the dichromate method (GB 11914-89) (see Figure 5 and 6 ). It can be expressed as the measurement of SO4 by the absorbance of the solution using a UV spectrophotometer. 2- The concentration of COD and SO4 in the control and example microbial fuel cells was calculated. 2- Removal performance (see Figure 7 ).

[0069] Figure 5(a) The power density of the microbial fuel cells with four anode materials first increases with the increase of current density. When the current density is too large, that is, when the external resistor is replaced with a small resistor, the voltage across the resistor drops too much, resulting in a decrease in power density. In the process of replacing the large resistor with a small resistor, the voltage of the battery gradually decreases. When the external resistor is modulated to 1000Ω, the battery voltages of carbon paper (CP), PANI-CP, PANI / WO3-CP and PANI / WS2 / WO3-CP are 0.474V, 0.526V, 0.550V and 0.585V, respectively. The voltage of the MFC with PANI / WS2 / WO3 as the anode drops the slowest, indicating that the equivalent resistance inside the battery is the smallest. At the same time, the MFC configured with PANI / WS2 / WO3 also exhibits the highest power density, about 2.98W / m 2 , slightly higher than 2.62W / m of PANI / WO3 2 , much higher than the 2.06W / m of PANI-CP and carbon paper. 2 and 1.87W / m 2 , indicating that the PANI / WS2 / WO3-CP bioanode has the best power generation performance.

[0070] From (b), we can observe that the cathode potential of the four microbial fuel cells slowly decreases with increasing current density. In contrast, the anode potential of these four microbial fuel cells increases significantly with increasing current density. Clearly, changes in anode potential are the primary cause of voltage variations in the microbial fuel cells. Under the same current density, the carbon cloth electrode exhibits the most pronounced potential increase, demonstrating the weakest resistance to polarization. The polarization curve for PANI / WS2 / WO3-CP has the lowest slope, indicating the strongest resistance to polarization and superior power generation performance.

[0071] After multiple cycles of liquid replacement and discharge, the bioanode of each microbial fuel cell was subjected to cyclic voltammetry test. The test results are as follows: Figure 6 (a) shows the PANI / WS2 / WO3-CP bioanode with the largest curve area, followed by PANI / WO3-CP, PANI-CP, and CP, indicating that the presence of microorganisms attached to the surfaces of the bioanodes did not alter the original order of electrochemical performance. This enhanced electrochemical activity can be attributed to both the attachment of microorganisms near the electrode and the properties of the electrode itself. On the one hand, due to the favorable biological properties of PANI, highly biocompatible electrodes modified with PANI readily encourage the formation of biofilms on the surface of electroactive microorganisms. On the other hand, composite electrodes such as PANI / WS2 / WO3-CP possess the ability to rapidly conduct electrons, interacting with the microorganisms in the redox reactions occurring on the electrode surface.

[0072] The impedance analysis and Nyquist curves of different bioanode materials are shown in Table 2. Figure 6 (b) The electron transfer capacity of the CP bioanode was significantly improved, with its charge transfer internal resistance dropping to 107.10Ω. Furthermore, the charge transfer internal resistances of the PANI / WS2 / WO3-CP, PANI / WO3-CP, and PANI-CP bioanodes were 5.3Ω, 11.60Ω, and 23.02Ω, respectively. PANI / WS2 / WO3-CP maintained the best electron transfer capacity among the four electrodes.

[0073] Depend on Figure 7 It can be seen that among the four types of microbial fuel cells with anode materials, the SO4 2- The PANI-modified carbon paper and WO3-CP also showed strong wastewater treatment performance, with sulfate removal rates reaching 86.79% and 90.08%, and COD removal rates reaching 85.75% and 88.36%, respectively. Table 1 summarizes the power density, COD removal efficiency, and sulfate removal efficiency of microbial fuel cells with different anode materials. As can be seen from Table 1, the PANI-composite materials all had higher power density, COD removal efficiency, and sulfate removal efficiency than the unloaded materials.

[0074] Table 1 Power density, COD removal efficiency and sulfate removal efficiency of microbial fuel cells with different anode materials

[0075] Bioanode materials Maximum power COD removal efficiency Sulfate removal efficiency CP 1.87 76.26 79.65 PANI-CP 2.06 85.75 86.79 <![CDATA[PANI / WO3-CP]]> 2.62 88.36 90.08 <![CDATA[PANI / WS2 / WO3-CP]]> 2.98 92.36 94.61

Claims

1. A method for preparing a polyaniline composite tungsten-based material, characterized by: A carbon paper electrode modified with a tungsten-based material is placed in an aniline solution, and ammonium persulfate solution is added dropwise with continuous stirring to allow polyaniline to grow uniformly in situ. After the reaction, drying is performed to obtain a polyaniline-composite tungsten-based semiconductor-modified carbon paper.

2. The method for preparing the polyaniline composite tungsten-based material according to claim 1, characterized in that: The tungsten-modified carbon paper electrode is a WO3-carbon paper or a WS2 / WO3-carbon paper electrode.

3. The method for preparing the polyaniline composite tungsten-based material according to claim 2, characterized in that: The preparation method of the WO3-carbon paper is as follows: S1. Dissolve 1 g of Na2WO4·2H2O and 0.63 g of C2H2O4·H2O in 100 mL of water, add 0.8 g of thiourea to the solution, stir evenly, and adjust the pH of the solution to 2 with hydrochloric acid to obtain a hydrothermal reaction solution; S2. The hydrothermal reaction solution in step S1 is placed in a hydrothermal reactor, the reactor is transferred to a blast drying oven, and the hydrothermal reaction is maintained at 160-200 ° C for 20-30h; S3. The black solid obtained by the reaction was filtered and repeatedly washed with deionized water and ethanol; the solid was then dried to obtain WO3 nanoparticle material; S4. 7.5 mg of WO3 rice particles were mixed with 60 μL of 5 wt% Nafion solution, 340 μL of deionized water, and 600 μL of anhydrous ethanol, and ultrasonically treated to obtain a dispersion; the dispersion was added dropwise onto the treated carbon paper, and then the carbon paper was dried to obtain WO3-carbon paper.

4. The method for preparing the polyaniline composite tungsten-based material according to claim 2, wherein: The preparation method of the WS2 / WO3-carbon paper is as follows: S1. Dissolve 1 g of Na2WO4·2H2O and 1.26 g of C2H2O4·H2O in 100 mL of water, add 1.6 g of thiourea to the solution, stir evenly, and adjust the pH of the solution to 1 with hydrochloric acid to obtain a hydrothermal reaction solution; S2. The hydrothermal reaction solution in step S1 is placed in a hydrothermal reactor, the reactor is transferred to a blast drying oven, and the hydrothermal reaction is maintained at 160-200 ° C for 20-30h; S3. The black solid obtained by the reaction was filtered and repeatedly washed with deionized water and ethanol; the solid was then dried to obtain WS2 / WO3 nanoparticle material; S4. 7.5 mg of WS2 / WO3 particles were mixed with 60 μL of 5 wt% Nafion solution, 340 μL of deionized water, and 600 μL of anhydrous ethanol, and ultrasonically treated to obtain a dispersion. The dispersion was added dropwise onto the treated carbon paper, and then the carbon paper was dried to obtain WS2 / WO3-carbon paper.

5. The method for preparing the polyaniline composite tungsten-based material according to claim 1, wherein: The concentration of the ammonium persulfate solution is 0.4 mol / L, and the concentration of the aniline solution is 0.1 mol / L; the volume ratio of the dropwise added ammonium persulfate solution to the aniline solution should be 1:

4.

6. The method for preparing the polyaniline composite tungsten-based material according to claim 1, characterized in that: The ammonium persulfate solution was added dropwise and stirred for 2 hours. After the reaction was completed, the electrode was taken out and rinsed thoroughly. Finally, the washed electrode was transferred to a blast drying oven and dried at 60° C. for 10 hours to obtain a polyaniline composite tungsten-based material.

7. A polyaniline composite tungsten-based material obtained by the method of claim 1, characterized in that: The polyaniline composite tungsten-based material with a nano-flower-like structure is obtained according to the method of claim 1.

8. Use of the polyaniline composite tungsten-based material according to claim 7, characterized in that: The polyaniline composite tungsten-based material is used in preparing anode materials for microbial fuel cells.

9. Use of the polyaniline composite tungsten-based material according to claim 7, characterized in that: The polyaniline composite tungsten-based material is used in the preparation of anodes for microbial fuel cells.

10. An application of the polyaniline composite tungsten-based material according to claim 7, characterized in that: Application of the polyaniline composite tungsten-based material in removing pollutants in the environment.